Impact of changing road infrastructure on children's active travel: A multi-methods study from Auckland, New Zealand. (September 2020) - Smith, Melody; Hawley, Greer; Mackay, Lisa; Hosking, Jamie; Mackie, Hamish; Ikeda, Erika; Egli, Victoria; Ellaway, Anne; Witten, Karen
Abstract: Introduction: Built environment infrastructure that supports active travel may help increase rates of children's active travel to school. Knowledge gaps exist in terms of how small-to-medium scale, school-focused infrastructural changes might impact children's active school travel and associated variables along the pathway to behaviour change. The aim was to work with a regional transport agency to evaluate the impact of infrastructural changes in a school neighbourhood. Methods: Children in school years 5–8 and their parents/caregivers from two schools involved in a school travel intervention were invited to participate. The study area was identified in partnership with Auckland Transport (responsible for delivering all intervention elements). Children completed a geographic informations systems survey that captured behaviours and neighbourhood perceptions. Parents completed a telephone interview to measure neighbourhood perceptions and reasons for school travel mode. Tube counters and video cameras were used to measure traffic speeds and volume, and counts of pedestrians and cyclists, respectively. Baseline measures were taken in 2015 (traffic data) and from May-July 2016 (all other measures), infrastructural works were delivered from November 2016 to May 2017, and follow-up measures were repeated in May-June 2018. Results: At baseline, 123 children and 88 parents participated. At follow-up, 152 children and 91 parents participated. Reductions in traffic speeds but increases in traffic volumes were observed post the intervention. Positive and negative shifts in child and parent neighbourhood perspectives were observed. Distance to school, convenience, and traffic saftey concerns were raised as key factors of importance by parents and children. Overall, rates of car use for the school trip increased, while video observation showed an increase in pedestrians. Conclusions: Reversing declines in active travel may require more intensive, community-wide interventions that substantially improve neighbourhood safety and perceptions of safety. Longer term follow-up may be necessary to understand the true effect of the intervention. Highlights: The impact of infrastructural interventions on active school travel was assessed. Objective traffic variables and parent and child perceptions were measured. Travelling to school by car increased following the intervention. More pedestrians were observed in the neighbourhood post the intervention. Safety from traffic, distance to school and convenience were important factors.